2013
DOI: 10.1172/jci68127
|View full text |Cite
|
Sign up to set email alerts
|

Collagen VII plays a dual role in wound healing

Abstract: Although a host of intracellular signals is known to contribute to wound healing, the role of the cell microenvironment in tissue repair remains elusive. Here we employed 2 different mouse models of genetic skin fragility to assess the role of the basement membrane protein collagen VII (COL7A1) in wound healing. COL7A1 secures the attachment of the epidermis to the dermis, and its mutations cause a human skin fragility disorder coined recessive dystrophic epidermolysis bullosa (RDEB) that is associated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
170
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(184 citation statements)
references
References 58 publications
(67 reference statements)
11
170
0
3
Order By: Relevance
“…To conclusively demonstrate that retention of cochlin in lymphoid conduits depended on collagen VII, we systemically ablated Col7a1 expression in a tamoxifen-inducible Col7a1 knockout mouse (1). In accordance with the previously established half-life of collagen VII (38), tamoxifen treatment led to a significant loss of collagen VII in skin and spleen after >10 wk (Fig.…”
Section: Collagen VII Is Indispensable For Retention Of Cochlin In Lymentioning
confidence: 62%
See 4 more Smart Citations
“…To conclusively demonstrate that retention of cochlin in lymphoid conduits depended on collagen VII, we systemically ablated Col7a1 expression in a tamoxifen-inducible Col7a1 knockout mouse (1). In accordance with the previously established half-life of collagen VII (38), tamoxifen treatment led to a significant loss of collagen VII in skin and spleen after >10 wk (Fig.…”
Section: Collagen VII Is Indispensable For Retention Of Cochlin In Lymentioning
confidence: 62%
“…For the studies, samples from human individuals with molecularly confirmed severe generalized recessive RDEB were used, as well as two genetic mouse models, the collagen VII hypomorphic RDEB mouse and a tamoxifen-inducible Col7a1 knockout mouse (1). The RDEB mouse shows all major signs of severe RDEB (25), and the tamoxifen-inducible Col7a1 knockout mouse allows targeted ablation of Col7a1 expression in time and space (1). RDEB is a progressive disease.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations